ERPNext for Effective Budgeting: Overcoming Project Financial Management Challenges in System Integrator Company - Azka, Aditya Fadillah; Nurul Aisyah (ADPEBI, 2024)
The process of implementing system integration by a system integrator company is a complex activity and requires good coordination between the various departments involved. The use of Enterprise Resource Planning (ERP) systems can help system integrator companies to improve the efficiency and effectiveness of the system integration implementation process. The purpose of this study focuses on examining the benefits of using ERPNext in the budgeting implementation process by system integrator companies. This study analyzes primary data in the company through an applied research approach. Data was collected through in-depth budgeting implementation interviews with key informants at system integrator companies that will use ERPNext. The results showed that the use of ERPNext in the budgeting process has several benefits, including: increasing the efficiency and effectiveness of the budgeting administrative process, improving collaboration and communication between departments involved in the project, increasing transparency and accountability of the project process, and improving the quality of project results.